2015
DOI: 10.1002/anie.201505918
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Synthesis of (Hetero)Aryl Alkyl Sulfones from (Hetero)Aryl Boronic Acids, Unactivated Alkyl Halides, and Potassium Metabisulfite

Abstract: A palladium-catalyzed one-step synthesis of (hetero)aryl alkyl sulfones from (hetero)arylboronic acids, potassium metabisulfite, and unactivated or activated alkylhalides is described. This transformation is of broad scope, occurs under mild conditions, and employs readily available reactants. A stoichiometric experiment has led to the isolation of a catalytically active dimeric palladium sulfinate complex, which was characterized by X-ray diffraction analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(44 citation statements)
references
References 43 publications
2
41
0
Order By: Relevance
“…We recently initiated a program exploring the catalytic introduction of sulfur dioxide into organic molecules, 13 and during the development of a palladium-catalyzed sulfinylative route to diaryl sulfones, 14 we observed the formation of desulfinylated side-products, resulting in biaryl formation. Significantly, these side-products were more common when heterocycle-derived sulfinates were implicated as intermediates, relative to the corresponding carbocyclic variants.…”
Section: Resultsmentioning
confidence: 99%
“…We recently initiated a program exploring the catalytic introduction of sulfur dioxide into organic molecules, 13 and during the development of a palladium-catalyzed sulfinylative route to diaryl sulfones, 14 we observed the formation of desulfinylated side-products, resulting in biaryl formation. Significantly, these side-products were more common when heterocycle-derived sulfinates were implicated as intermediates, relative to the corresponding carbocyclic variants.…”
Section: Resultsmentioning
confidence: 99%
“…Because arylboronic acids are compatible with alkylhalides, Shavnya et al. demonstrated for the first time in 2015, the preparation of sulfones in a single step from SO 2 surrogates . Interestingly, air‐ and moisture‐stable organosilanes could also be used for the synthesis of sulfones using a copper(I) oxide as catalyst with SO 2 surrogates and alkylhalides .…”
Section: Methodsmentioning
confidence: 99%
“…This strategy has been successfully applied by Willis and co-workers,w ho were able to generate sulfinate anions from SO 2 surrogates (e.g., DABCO·(SO 2 ) 2 (DABSO), K 2 S 2 O 5 )with arylmagnesium and aryllithium species. [6] Forexample,arylsulfinates were obtained from boronic acids,u sing palladium and gold catalysts. [6] Forexample,arylsulfinates were obtained from boronic acids,u sing palladium and gold catalysts.…”
mentioning
confidence: 99%
“…[5] Using stoichiometric or catalytic quantities of metal compounds,the method has then been extended to milder nucleophiles,such as organozinc and organoboron reagents,t oimprove the funtional-group tolerance. [6] Forexample,arylsulfinates were obtained from boronic acids,u sing palladium and gold catalysts. [7] Because arylboronic acids are compatible with alkylhalides,Shavnya et al demonstrated for the first time in 2015, the preparation of sulfones in as ingle step from SO 2 surrogates.…”
mentioning
confidence: 99%